(untitled) (Medical Forum Monthly, 2022)
Objective: To compare the effect of whole walnut and walnut leaf extract (Aqueous and Ethanolic) on lipid profile and atherogenic index in Hypercholesterolemic rats. Study Design: Experimental study Place and Duration of Study: This study was conducted at the Islamic International Medical College, Riphah International University, in collaboration with National Institute of Health and Citilab, Islamabad, Pakistan from January to June 2015. Materials and Methods: A total of 50 Sprague Dawley rats were in divided in five groups, HC (hypercholesterolemic control), WW (Whole walnut), AE (Aqueous extract), and EE (Ethanolic extract). Serum cholesterol, triglycerides, LDL, HDL and atherogenic ratios LDL/HDL and TC/HDL were measured at baseline, 8 and 12 weeks respectively after inducing hypercholesterolemia. Data was analyzed by ANOVA and student t test using SPSS version 19. P value of <0.05 was considered statistically significant. Results: WW in comparison to AE group decreased serum triglycerides (p=0.01) and serum total cholesterol in (p=0.02). WW in comparison to EE group decreased only serum triglycerides significantly among all lipid profile parameters (p=0.00). A significant decrease in serum total cholesterol (p=0.00) and an increase in serum HDL (p=0.00) by EE was observed compared to AE group. Conclusion: WW, AE and EE have specific effects on individual lipid profile parameters which is hypolipidemic as all three decreased bad cholesterol and raised the good HDL lipoproteins. Further research can delineate this therapeutic potential in cardiovascular diseases.